FEATURES OF THE OCCURRENCE OF CARDIO COMORBIDITY IN ARTERIAL HYPOTENSION IN THE FORM OF ISCHEMIC HEART DISEASE (Conferencea, 2023)
It is to study the epidemiological features of the occurrence of cardio comorbidity in the form of ischemic heart disease in arterial hypotension (ArGt).